Groundwater management and ownership: rejoinder: discussion - Shah, Tushaar (2008)
Although a lot more needs to be done to evolve a better strategy for managing the groundwater economy, a copybook transposition of the Californian and Spanish formula as argued in these columns 'Groundwater Management and Ownership' (February 16) seems na?ve, even disingenuous. A groundwater governance regime for a country like India cannot be dealt with only from the earth science perspective but involves a broader grasp of the organisation of the groundwater economy and its underlying socio-economic dynamics.